2003 Handbook of Employment Regulations Affecting Florida Farm Employers and Workers: Migrant Labor Housing [State] - Leo C. Polopolus; Michael T. Olexa; Fritz Roka; Carol Fountain (EDIS)
Migrant labor housing regulations  provide State standards for migrant labor camps and/or residential migrant housing facilities. This is EDIS document FE405, a publication of the Department of Food and Resource Economics, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida, Gainesville, FL. Published July 2003. This information is included in Circular 1200, Handbook of Employment Regulations Affecting Florida Farm Employers and Workers.